SPIRITUALITAS PEREMPUAN BERZINA: Analisis SosioHistoris terhadap teks Yohanes 8:1-11 - Sipora Blandina Warella (TANGKOLEH PUTAI, 2020)
Women who commit adultery in the construct of Jewish religious structures are not taken into account. This is because the role and function of adulterous women in society according to the Law of Moses is not correct. Women who commit adultery are judged to have no spirituality. Adultery women are in a discriminatory position. In this study, the researcher used qualitative research methods, in this case, literature review with socio historical analysis to examine it using Piedmont's theory of spirituality and found that the spirituality dialogue of Jesus or sharing spirituality with adulterous women is oriented towards the transformation of humanity. The author realizes that research into the spirituality of women who commit adultery in this text remains limited and requires further research.